Mahasiswa Migran Pembawa Kabar Baik: Pendekatan Teologi Pastoral Model Sintesis Stephen B. Bevans Bagi Mahasiswa Asal Atambua-Timor Di Universitas Tribhuwana Tungga Dewi Malang - Hendy, Siprianus (Perspektif, 2023)
This article discusses the problem of migrant students in Malang City. Spe[1]cifically, this article wants to offer a pattern of approach to theology for migrant students from Atambua who study at Tribhuana Tungga Dewi University, Malang. The research method used is descriptive qualitative with interview data collection techniques and literature study. The results obtained are that migrant students from Atambua have complex problems such as a lack of recognition of the locus of learning, community perceptions that hinder the socialization process, and economic problems related to the availability of employment opportunities. In this regard, the Church is called to take part in the journey of these students.